Comparative study between the use of isosorbide dinitrate and captopril in hypertensive emergency treatment. - Brandy Viera Valdés (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Fundament: Oral antihypertensive drugs are lacking in our environment at present in tog hypertensive urgencies, that is why new therapeutic alternatives are necessary to treat this medical problem. Objective: To assess the effect of Isosorbide Dinitrate in the treatment of hypertensive urgencies the system of urgencies. Method: a cuasi experimental study was designed with 60 patients with this diagnosis. The patients were divided into two groups. The patients of one group received treatment for the hypertensive crisis with Isosorbide Dinitrate 10 mg sub lingually and the others had their treatment with Captopril 25 mg p.o. Results: The response of the treatment with Isosorbide Dinitrate with similar to the treatment with Captopril. High Blood Pressure was controlled in 66,6 % with Isosorbide Dinitrate and in 73,3 % with Captopril, with few effects for both medications. Conclusions: Results were similar in this search with the use of Isosorbide Dinitrate and other antihypertensive drugs in the treatment of hypertensive urgencies . In the future, with the appearance of new evidencies Isosorbide Dinitrate could be used as an alternative in the treatment of hypertension at the urgency department when there is no possibility for applying any other medication.